1993
DOI: 10.1007/bf00204626
|View full text |Cite
|
Sign up to set email alerts
|

Can anti-IgE be used to treat allergy?

Abstract: A summary of the properties of CGP 51901 is shown in Table 3. On the basis of its binding to IgE and IgE-secreting cells and its activity in vitro and in vivo, CGP 51901 is expected to be able to decrease serum IgE by direct clearance of IgE and by reduction of the numbers and productivity of IgE-secreting cells. The end result of reduction of IgE in the circulation and on mast cells is expected to be the attenuation of IgE-mediated reactions and the improvement in allergy symptoms. The effective serum concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 42 publications
3
56
0
Order By: Relevance
“…CGP 51901 is composed of the variable heavy (H) and light (L) chain regions of TES-C21 linked to the human ␥1 and constant regions. It has been shown to have the same binding properties as its parent murine antibody (18) and in vitro studies have demonstrated that it does not bind to other immunoglobulin isotypes nor to other circulating cells (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CGP 51901 is composed of the variable heavy (H) and light (L) chain regions of TES-C21 linked to the human ␥1 and constant regions. It has been shown to have the same binding properties as its parent murine antibody (18) and in vitro studies have demonstrated that it does not bind to other immunoglobulin isotypes nor to other circulating cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…CGP 51901 was developed from an antibody selected from a panel of murine antibodies generated against human IgE (18). The parent antibody (TES-C21) was shown to bind with high affinity to free IgE and IgE expressed on the surface of B cells but not to induce histamine release from IgE-bearing basophils (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human basophil studies have shown that FcεRI expression is regulated by the level of free IgE, so that reduced levels of free IgE should lead to lower densities of FcεRI on basophils and mast cells and lowered sensitivities [19,38,39]. And, anti-IgE may lead to the down-regulation of IgE production by eliminating or down-regulating IgE-expressing B cells, perhaps by cross-linking membrane-bound IgE and causing apoptosis or anergy [37,40] or perhaps by complement-mediated and cell-mediated cytolysis [41]. It has been difficult to demonstrate reduction of IgE-producing B cells in the clinical trials with monoclonal antibodies, but other in vivo and in vitro experimental results are supportive of an anti-IgE-expressing B cell mechanism [18].…”
Section: Discussionmentioning
confidence: 99%